2015
DOI: 10.1016/j.eja.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficient rates of nitrogenous fertiliser for irrigated sweet sorghum cultivation during the post-rainy season in the semi-arid tropics

Abstract: Sorghum (Sorghum bicolor (L.) Moench) is a multipurpose crop with high tolerance to environmental stresses. To meet the increased demand for food and biofuel, current agricultural practices rely on the excessive use of inorganic nitrogen (N) fertiliser. However, excessive N fertiliser has resulted in negative environmental effects. In view of the varied N use efficiency (NUE) of plants under different environmental conditions, the aim of this study was to evaluate the efficient rates of N fertiliser in semi-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This study showed that within a certain range of W&N, the crops yield and NI grow with the increase of W&N input, yet the yield and NI had a tendency to decrease when exceeding a certain threshold, so that only suitable W&N conditions could guarantee the highest yield and NI. The same conclusion has been drawn by other scholars [29][30][31][32] . Since the irrigation and fertilization has changed the soil's water and nutrient environment, there has been a positive correlation between root growth and soil moisture status within a certain range.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that within a certain range of W&N, the crops yield and NI grow with the increase of W&N input, yet the yield and NI had a tendency to decrease when exceeding a certain threshold, so that only suitable W&N conditions could guarantee the highest yield and NI. The same conclusion has been drawn by other scholars [29][30][31][32] . Since the irrigation and fertilization has changed the soil's water and nutrient environment, there has been a positive correlation between root growth and soil moisture status within a certain range.…”
Section: Discussionsupporting
confidence: 88%
“…1) and apparent N recovery efficiency (ANRE) (Eq. 2) were calculated according to Kurai et al (2015).…”
Section: Plant Growth Leaf Gaseous Exchange Shoot N and N Use Effimentioning
confidence: 99%
“…In this respect, it is expected that increased mineral N forms in the soil solution in phenological stages of higher root emission contributes to the increase in N uptake and shoot content. This promotes an increase in photosynthetic rate, because N is an essential component of ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) and a key enzyme in carbon fixation (Kitajima et al 1997;Fyllas et al 2009), and results in higher N use efficiency (Kurai et al 2015). Nitrogen deficiency due to low availability in soil reduces chlorophyll content, compromises the photosynthetic process, and reduces dry matter and grain yield (Kirkby 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another study applying nitrogen fertilizers at the level of 90-120 kg N ha -1 showed an increase in the growth of sorghum production (Uchino et al, 2013). The response of sorghum to nitrogen fertilizer depends on genotype, climatic conditions, and the nature of the soil (Kurai et al, 2015). The novelty of this study is the use of new BMR sorghum mutant line material as a result of mutation technology produced in Indonesia.…”
Section: Introductionmentioning
confidence: 99%